A Cretaceous origin for fire adaptations in the Cape flora - He, Tianhua; Lamont, Byron; Manning, J. (Nature Publishing Group, 2016)
Fire has had a profound effect on the evolution of worldwide biotas. The Cape Floristic Region is one of the world's most species-rich regions, yet it is highly prone to recurrent fires and fire-adapted species contribute strongly to the overall flora. It is hypothesized that the current fire regimes in the Cape could be as old as 6-8 million years (My), while indirect evidence indicates that the onset of fire could have reached 18 million years ago (Ma). Here, we trace the origin of fire-dependent traits in two monocot families that are significant elements in the fire-prone Cape flora. Our analysis shows that fire-stimulated flowering originated in the Cape Haemodoraceae 81 Ma, while fire-stimulated germination arose in the African Restionaceae at least 70 Ma, implying that wildfires have been a significant force in the evolution of the Cape flora at least 60 My earlier than previous estimates. Our results provide strong evidence for the presence of fire adaptations in the Cape from the Cretaceous, leading to the extraordinary persistence of a fire-adapted flora in this biodiversity hotspot, and giving support to the hypothesis that Cretaceous fire was a global phenomenon that shaped the evolution of terrestrial floras.